Airworthiness and No Fault Found - Lacey, Laura (Cranfield University, 2022)
Excel spreadsheet with the results from a questionnaire aimed at aircrew on their experience and knowledge of no fault found and its impact on airworthiness.
Keywords: 'No Fault Found'; 'Airworthiness'; 'Air safety'